Methodology for Improving Health Insurance Mechanisms in Result-Oriented Budgeting - Ishmanova Diana Nurmamadovna PhD (Scientific Trends, 2025)
In this article, the economic essence of OFB and its role in the management of the state budget, the current state of state budget expenditure planning, the role and essence of medical insurance in healthcare institutions are analyzed.
Keywords: Result-oriented budgeting, the importance of health insurance in the financing of health care facilities.